Estudio de prefactibilidad para la instalación de una planta productora de bebida energética gasificada a base de maca negra, hoja de coca y arándano - Agramonte Mendiola, Diego Armando (2016)
The purpose of the present investigation is the study for the installation of a production plant of gasified energy drink, a refreshing soft drink made with black maca, coca leaves, and blueberries; resources from the Peruvian regions of Junín, Cusco and La Libertad respectively. The product constitutes a healthy alternative to the wrongly called “energy” drinks that are only stimulators; this alternative possesses health benefits and properties, apart from being a real energy drink, which guaranties a sustained energy release.